Computer-aided graphing and simulation tools for AutoCAD users - Simionescu, P. A. 1968- (Chapman & Hall/CRC computer and information science series, 2015)
This book allows readers to expand the versatility of AutoCAD® design and documentation software. It provides ready-to-use procedures and computer programs for solving problems in a variety of application areas, including computer-aided design, data visualization, evolutionary computation, numerical methods, single and multicriteria optimization, linkage and robot kinematics, cam mechanisms, and involute gears